ANALYSIS TYPES AND FUNCTIONS OF TABOO WORDS IN “THE WOLF OF WALL STREET” MOVIE - Dewi Putri Rahmayani; Fitrawati Fitrawati (English Language and Literature, 2018)
In linguistics, everyone has his own way of expressing his feelings. One such way is by using taboo language. Taboo language not only happens in everyday life, but also in a movie. This study aims to find the types of taboo language as well as the functions contained in every utterance used by the characters in the western film entitled "The Wolf of Wall Street". The data of this research are in the form of sentence or utterance containing taboo language which is spoken by every character in the film. The data were collected from the film "The Wolf of Wall Street" taken from the www.layarkaca21.com. Then, choose the utterances containing the taboo language and grouped them into types and functions of taboo words. Type of the research is qualitative and quantitative research. Based on data analysis, it was found that there are 3 types of taboo languages with the highest percentage in the movie "The Wolf of Wall Street" namely; Obscenity(64,8%),Epithets(13,1%), and Vulgarity (8,2%). For the function of the use of taboo language wasfound 3 functions with the highest percentage as well. They areto creation of strong interpersonal (35,6%), provide catharsis (24,5%), and to draw attention to oneself (17,8%).